Kegelina: a new limnic ostracod (Cyprideidae, Cypridoidea) genus from the Lower Cretaceous of the Americas and Africa. (July 2014) - Neto, João Villar de Queiroz; Sames, Benjamin; Colin, Jean-Paul
Abstract : The non-marine Lower Cretaceous ostracod genus Kegelina new genus (Cypridoidea, Cyprideidae) is known from South America (Bahia state, eastern Brazil), West Africa (Gabon and 'Congo'), and North America (Montana, Idaho and Wyoming, U.S.A.). It comprises five species: Kegelina anomala (Peck, 1941) new combination, Kegelina armata (Krömmelbein, 1962) new combination, Kegelina bisculpturata (Wicher, 1959) new combination, Kegelina depressa (Moura, 1972) new combination, and Kegelina kegeli (Wicher, 1959) new combination, all of which having formerly been described as representatives of Cypridea Bosquet, 1852. The closer relationships of Kegelina new genus among the Cyprideidae Martin, 1940 are discussed. Other potential species of Kegelina n. gen. are presumed to occur in northeastern China and Europe but remain to be examined.